Potret Kegelisahan Sekolah dalam Melaksanakan Ujian Nasional - Zamroni, M. Imam (Unisia, 2012)
The policy of National Examination (NE) standardisation has caused schools to be trapped in a practical effort to help student to be passed, focussing on merely repetitive test practices of examination subjects. Learning has been considered not as a process of developing or maturing, but a process to gain high grades and to pass the NE. As a consequence, teaching-learning process has resulted in fear of failing the NE for studets. Teachers have also been stressed and depressed, because on one hand they have cultivated social empathy, but on the other hand, they have been forced to engage in practices even they have not believed in, and in search for ‘bypasses’ for the sake of students’ successful in NE. Therefore, the policy of standardisation of passing grades in the NE should be changed to reflect the spirit of decentralization and regional autonomy, and the appreciation of diversity of school qualities and capacities for teaching-learning. Keywords: Policy, National Examination, pass, fear.